Accounting and Recommendations for Reducing and Optimizing Period Expenses in Business Entities Based on International Standards (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is based on the relevance of cost accounting in business entities. The targeted use of material, financial and labor resources enables organizations to get more profit and benefits. The volume of resources is decreasing as a result of the global economic crisis. And this makes it relevant to make rational use of the equipment, buildings, tools, inventory and financial resources available in the organization, and accounting of Uzbekistan and to improve reporting on financial results.